Pendampingan Penguatan Kepatuhan Syariah Bagi Marketing BMT Bina Ihsanul Fikri Yogyakarta - Riduwan Riduwan; Akhmad Arif Rifan; Rofiul Wahyudi (AKM, 2023)
Sharia compliance is a requirement for Islamic financial institutions because it can increase public trust. As part of an Islamic financial institution, Baitul Maal wa Tamwil (BMT) is required to maintain consistency in implementing Sharia compliance, both in operations and marketing. The Sharia principle that forms the primary basis is the fatwa of the National Sharia Council (DSN), the Indonesian Ulema Council (MUI). The fatwa is binding on all financial institutions, including BMT. Therefore all employees must master and implement it at work.Community service in the form of assistance in Strengthening Sharia Compliance at BMT Bina Ihsanul Fikri Marketing has succeeded in increasing understanding of Sharia principles and marketing commitment to its implementation—mentoring methods in focus group discussions and classical training with structured material. The training was conducted for marketing as many as 56 people. The assistance results show an increase in understanding of Sharia principles by 85.5% and a commitment to implement Sharia principles by 89.3% properly.